2006
DOI: 10.1007/s10336-005-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the study of genetic variation in migratory behaviour

Abstract: Evolutionary change results from selection acting on genetic variation. For migration to be successful, many different aspects of an animal's physiology and behaviour need to function in a co-coordinated way. Changes in one migratory trait are therefore likely to be accompanied by changes in other migratory and lifehistory traits. At present, we have some knowledge of the pressures that operate at the various stages of migration, but we know very little about the extent of genetic variation in various aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 85 publications
1
73
0
Order By: Relevance
“…However, we cannot assume that these responses will necessarily improve the probability of persistence without a better understanding of reaction norms for speciWc traits within individual species (van Noordwijk et al 2006). Furthermore, climate and land-use changes could adversely aVect migratory birds through decoupling of the proximate cues and ultimate processes that aVect migratory decisions (Coppack and Both 2002;Gienapp and Visser 2006).…”
Section: Discussionmentioning
confidence: 98%
“…However, we cannot assume that these responses will necessarily improve the probability of persistence without a better understanding of reaction norms for speciWc traits within individual species (van Noordwijk et al 2006). Furthermore, climate and land-use changes could adversely aVect migratory birds through decoupling of the proximate cues and ultimate processes that aVect migratory decisions (Coppack and Both 2002;Gienapp and Visser 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Common garden experiments allow us to draw inferences about genetic changes in wild populations if experimental conditions are strictly controlled and do not change over time (15,63). To achieve this, we collected nestlings at an early age, hand-raised them, and studied birds in climate-controlled chambers in captivity, which allowed us to follow a highly standardized protocol for rearing, keeping, and measuring birds throughout the complete study from 1988 through 2002.…”
Section: Methodsmentioning
confidence: 99%
“…These syndromes rely on a suite of phenotypic traits that co-evolve to determine the behavioural types of individuals. Such syndromes have been extensively studied in the context of migration because migration implies selection on morphological characters for long distance movements (Van Noordwijk et al, 2006) resulting in different characteristics between migrant and resident individuals (Sandberg and Moore, 1996;Lõhmus et al, 2003;Marchetti and Zehtindjiev, 2009). For example, Leisler and Winkler showed that migrant birds are generally smaller and have shorter tails and longer wings than non-migrant individuals (Leisler and Winkler, 2003).…”
Section: Relationship With Flight Performancementioning
confidence: 99%